In his father's footsteps : a novel - Steel, Danielle; Miller, Dan John (Prince Frederick, MD : Recorded Books, 2018)
The story of two World War II concentration camp survivors, the life they build together, and the son who faces struggles of his own as a first generation American determined to be his own person and achieve success.
Title from container.
Recordable compact discs.
Read by Dan John Miller.
Keywords: Adult children of immigrants -- Fiction; Americanization -- Fiction; Immigrants -- New York (State) -- New York -- Fiction; American Dream -- Fiction; Fathers and sons -- Fiction; Social mobility -- United States -- 20th century -- Fiction; Wealth -- Moral and ethical aspects -- 20th century -- Fiction; Wealth -- Psychological aspects -- 20th century -- Fiction; Lower East Side (New York, N.Y.) -- Fiction; Audiobooks; Historical fiction